Iron‐Catalyzed Carbonylation Reactions with Carbon Monoxide - Sun, Kangkang; Lu, Guo‐Ping; Han, Wei; Beller, Matthias (Angewandte Chemie International Edition, 2025)
The utilization of carbon monoxide (CO) as an inexpensive and indispensable C 1 feedstock for the efficient construction of diverse carbonylated compounds has been a subject of numerous studies for decades. Nowadays, transition metal‐catalyzed carbonylation represents a pivotal synthetic approach for the generation of carbonyl‐containing molecules. Among the known catalysts for these transformations, non ‐noble metal‐based systems have garnered increasing interest in recent years due to their substantial advantages, including wide availability, low cost, and low toxicity. In this review, we have summarized and discussed original and recent developments in iron‐catalyzed carbonylative transformations, wherein CO is utilized as the C 1 feedstock.